Adaptor SH3BGRL drives autophagy-mediated chemoresistance through promoting PIK3C3 translation and ATG12 stability in breast cancers. Issue 8 (3rd August 2022) - Zhang, Shaoyang; Liu, Xiufeng; Abdulmomen Ali Mohammed, Saleh; Li, Hui; Cai, Wanhua; Guan, Wen; Liu, Daiyun; Wei, Yanli; Rong, Dade; Fang, Ying; Haider, Farhan; Lv, Haimei; et al.
ABSTRACT: Acquired chemotherapy resistance is one of the main culprits in the relapse of breast cancer. But the underlying mechanism of chemotherapy resistance remains elusive. Here, we demonstrate that a small adaptor protein, SH3BGRL, is not only elevated in the majority of breast cancer patients but also has relevance with the relapse and poor prognosis of breast cancer patients. Functionally, SH3BGRL upregulation enhances the chemoresistance of breast cancer cells to the first-line doxorubicin treatment through macroautophagic/autophagic protection. Mechanistically, SH3BGRL can unexpectedly bind to ribosomal subunits to enhance PIK3C3 translation efficiency and sustain ATG12 stability. Therefore, inhibition of autophagy or silence of PIK3C3 or ATG12 can effectively block the driving effect of SH3BGRL on doxorubicin resistance of breast cancer cells in vitro and in vivo. We also validate that SH3BGRL expression is positively correlated with that of PIK3C3 or ATG12, as well as the constitutive occurrence of autophagy in clinical breast cancer tissues. Taken together, our data reveal that SH3BGRL upregulation would be a key driver to the acquired chemotherapy resistance through autophagy enhancement in breast cancer while targeting SH3BGRL could be a potential therapeutic strategy against breast cancer. Abbreviations: ABCs: ATP-binding cassette transporters; Act D: actinomycin D; ACTB/β-actin: actin beta; ATG: autophagy-related; Baf A1 : bafilomycin A1 ; CASP3: caspase 3; CHX: cycloheximide; CQ: chloroquine; Dox: doxorubicin; FBS: fetal bovine serum; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GEO: gene expression omnibus; GFP: green fluorescent protein; G6PD: glucose-6-phosphate dehydrogenase; GSEA: gene set enrichment analysis; IHC: immunochemistry; KEGG: Kyoto Encyclopedia of Genes and Genomes; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; 3-MA: 3-methyladenine; mRNA: messenger RNA; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; SH3BGRL: SH3 domain binding glutamate-rich protein-like; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like autophagy activating kinase 1